Resonant interaction of electromagnetic wave with plasma layer and overcoming the radiocommunication blackout problem. (12th April 2018) - Bogatskaya, A V; Klenov, N V; Tereshonok, M V; Adjemov, S S; Popov, A M
Abstract: We present an analysis of the possibility of penetrating electromagnetic waves through opaque media using an optical-mechanical analogy. As an example, we consider the plasma sheath surrounding the vehicle as a potential barrier and analyze the overcoming of radiocommunication blackout problem. The idea is to embed a «resonator» between the surface on the vehicle and plasma sheath which is supposed to provide an effective tunneling of the signal to the receiving antenna. We discuss the peculiarities of optical mechanical analogy applicability and analyze the radio frequency wave tunneling regime in detail. The cases of normal and oblique incidence of radiofrequency waves on the vehicle surface are studied.